Advanced solid state physics - Phillips, Philip (Philip W.). (Cambridge : Cambridge University Press, 2012)
'Providing an up-to-date and lucid presentation of phenomena across modern advanced-level solid state physics, this new edition builds on a basic understanding to introduce students to the key research with the minimum of mathematics. It covers cutting-edge topics, including electron transport and magnetism in solids. It is the first book to explain topological insulators and strongly correlated electrons. Explaining solid state physics in a clear and detailed way it also has 100 exercises for students to test their knowledge. In addition to the extensive discussion of magnetic impurity problems, bosonization, quantum phase transitions and disordered systems from the first edition, the new edition includes such topics as topological insulators, high-temperature superconductivity and Mott insulators, renormalization group for Fermi liquids, spontaneous symmetry breaking, zero and finite-temperature Green functions, and the Kubo formalism. Figures from the book and solutions to student exercises are available online at www.cambridge.org/solidstate'--
'Providing an up-to-date and lucid presentation of phenomena across modern advancedlevel solid state physics, this new edition builds on a basic understanding to introduce students to the key research with the minimum of mathematics. It covers cutting-edge topics, including electron transport and magnetism in solids. It is the first book to explain topological insulators and strongly correlated electrons. Explaining solid state physics in a clear and detailed way, it also has over 50 exercises for students to test their knowledge. In addition to the extensive discussion of magnetic impurity problems, bosonization, quantum phase transitions, and disordered systems from the first edition, the new edition includes such topics as topological insulators, high-temperature superconductivity and Mott insulators, renormalization group for Fermi liquids, spontaneous symmetry breaking, zero and finite-temperature Green functions, and the Kubo formalism'--
1. Introduction -- 2. Non-interacting electron gas -- 3. Born-Oppenheimer approximation -- 4. Second quantization -- 5. Hartree-Fock approximation -- 6. Interacting electron gas -- 7. Local magnetic moments in metals -- 8. Quenching of local moments: the Kondo problem -- 9. Screening and plasmons -- 10. Bosonization -- 11. Electron-lattice interactions -- 12. Superconductivity in metals -- 13. Disorder: localization and exceptions -- 14. Quantum phase transitions -- 15. Quantum hall and other topological states -- 16. Electrons at strong coupling: mottness.
Includes bibliographical references and index.
Keywords: Solid state physics